2014
DOI: 10.1002/anie.201408380
|View full text |Cite
|
Sign up to set email alerts
|

Stereodivergent Total Synthesis of Δ9‐Tetrahydrocannabinols

Abstract: All four stereoisomers of Δ(9)-tetrahydrocannabinol (Δ(9)-THC) were synthesized in concise fashion using stereodivergent dual catalysis. Thus, following identical synthetic sequences and applying identical reaction conditions to the same set of starting materials, selective access to the four stereoisomers of THC was achieved in five steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 74 publications
2
90
0
1
Order By: Relevance
“…Recently, Carreira et al. presented an elegant approach to the four stereoisomers of Δ 9 ‐THC by using stereodivergent dual catalysis in the key step 9. Efficient synthetic procedures for members of this important natural product class open the door for further investigations of the pharmacology of natural and—thanks to the synthesis approach—also unnatural isomers.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Carreira et al. presented an elegant approach to the four stereoisomers of Δ 9 ‐THC by using stereodivergent dual catalysis in the key step 9. Efficient synthetic procedures for members of this important natural product class open the door for further investigations of the pharmacology of natural and—thanks to the synthesis approach—also unnatural isomers.…”
Section: Methodsmentioning
confidence: 99%
“…228 in a moderately diastereoselective RCM using a substrate featuring diastereotopic vinyl groups) [604], the crotogoudin ring system [605], tetrahydrocannabinol derivatives (e.g. 229) [606], diaminocyclohexenes [607], maeocrystal V (an earlier step in the synthesis employs enantioselective rhodium carbene-mediated C-H activation) [608], tamiflu (e.g. 230) [609], 6-O-benzoylzeylenol [610], the cembranoid skeleton [611], cyclohexenes fused to polycycles (two-fold metathesis) (e.g.…”
Section: )mentioning
confidence: 99%
“…(À)-trans-D 9 -THC, the main causeo fp sychoactive effects of Cannabis,h as ah exahydro-6H-benzo [c]chromene core (violet color, 3)a nd exhibits high bindinga ffinity for the endocannabinoid receptors (CB 1 receptor:a bundanti nb rain; CB 2 receptor:a bundant in immune cells). [25,26] The chemical synthesis of (À)-trans-D 9 -THC and its analogs bearingt he benzo [c]chromene motif has extensively been investigated over last half-century, [27] and as eminalr eview on their synthesis has recently been reported by Carreira et al [24] On the other hand, (À)-CBD does not contain the benzo [c]chromene motif, and is structurally composed of three major parts:i .e.,l imonene (green), resorcinol (blue), and C4'-alkyl chain (red) parts (Figure 2; yellow circle). It is reported that (À)-CBD does not bind to the orthosteric sites of the CB 1 and CB 2 endocannabinoid receptors.…”
Section: Introductionmentioning
confidence: 99%